Parent-child relationship and level of openness of Filipino male adolescent homosexuals - Argonza, Estalker G. III; Belda, Edgar G. Jr (College of Home Economics, University of the Philippines Diliman, 2018)
Given the known characteristics of Filipino families and in light of the increasing awareness and acceptance of the Lesbian, Gay, Bisexual and Transgender LGBT movement in the country, the study investigated the Filipino male homosexuals 1. quality of parent child relationship, 2. level of openness to disclose their sexuality, and 3. the correlation of the two variables. The Parent Child Relationship Survey PCRS and the Outness Inventory OI were administered to 100 Filipino male adolescent homosexuals in Metro Manila. Pearson correlation coefficients were then calculated to assess the relation between the two variables, and p values were taken to analyze its significance. Results reveal that Filipino male adolescent homosexuals perceive higher quality of relationship with each of their parents as compared to Western male adolescents and that they have closer ties with their mothers than with their fathers. Moreover, Filipino male homosexuals have an average level of openness which means that the status of their sexual orientation is probably known by their parents but is rarely talked about. They also tend to disclose their sexuality to their mothers alone, or to their mothers first, before they would to their fathers. Finally, it was determined that there is a weak yet significant positive correlation between the father child relationship and the openness of the homosexual, but there is no significant relationship between the mother child relationship and the homosexual s openness. Potential explanations of the results and their implications in academic, social and political fields were also discussed.